2021
DOI: 10.1080/20008198.2021.1947002
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic and stressful life events in hoarding: the role of loss and deprivation

Abstract: Background: Although past research shows hoarding to be associated with stressful life events involving loss and/or deprivation, the temporal relationship between the onset of symptoms and these events is not completely clear. Objectives: In a cross-sectional online study, we examined the relationship between the number of events involving loss or deprivation before/simultaneously vs. after the onset of hoarding and various hoarding-related beliefs, such as emotional attachment to possessions, and symptom seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The current study found that negative life events can partly explain the relationship between childhood trauma and NSSI, which is the indirect path. Individuals with a history of childhood trauma often exhibit a lower capacity for environmental adaptation, demonstrating a relatively lower resilience to negative life events, such individuals experience a higher incidence of negative life events during adulthood, 40 , 41 which are viewed as potential risk factors for adolescent NSSI behaviors. 42 Adolescents are at a turning point in their life development.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that negative life events can partly explain the relationship between childhood trauma and NSSI, which is the indirect path. Individuals with a history of childhood trauma often exhibit a lower capacity for environmental adaptation, demonstrating a relatively lower resilience to negative life events, such individuals experience a higher incidence of negative life events during adulthood, 40 , 41 which are viewed as potential risk factors for adolescent NSSI behaviors. 42 Adolescents are at a turning point in their life development.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment process used for the present sample has been described in more detail elsewhere (Fontenelle et al, 2020). Individuals with hoarding problems were selected through advertisements in social media (i.e.…”
Section: Subjectsmentioning
confidence: 99%
“…The general characteristics of the present sample have been already described elsewhere (Fontenelle et al, 2020). Most volunteers were based at the US (n = 60; 53.1%), Australia (n = 25; 22.3%) or the UK (n = 17; 16.2%).…”
Section: Description Of the Samplementioning
confidence: 99%